Switching cost efficiency in capacitated multi-echelon multi-product distribution chain. (29th May 2009) - Regikumar, V.; Krishnankutty, K.V.
The movement of products in a multi-echelon supply chain accrue several cost elements at each stage. The product differentiation and proliferation activities occurring during the product advancement along the supply chain stages create mass customised multi-products with a certain amount of chain efficiency and agility. Some of the differentiation activities in the distribution chain echelons are the customised painting, packing and labelling. A significant cost associated with capacitated supply chain stage undertaking customisation activities is the switching cost which is driven by the limited resources and is similar to the set-up costs in production environment. Whenever customers switch over to a new product feature offered by the chain, one or more of the supply chain stages has to switchover the customisation facilities and this causes a switching cost input to the chain. One way of reducing switching costs faced by supply chains is to optimise the product sequence along the echelons. This paper initially discussed a mathematical model of a three echelon distribution chain requiring optimal sequencing decisions and later the model integrates two metaheuristics, i.e. Genetic Algorithm (GA) and Simulated Annealing (SA). The results reveal that simulated annealing overwhelms GA in terms of computational time.